2019
DOI: 10.22146/ijc.33765
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Extractable Petroleum Hydrocarbons by Consortia <i>Bacillus cereus</i> and <i>Pseudomonas putida</i> in Petroleum Contaminated-Soil

Abstract: Contamination of soil by the activities of exploration, production, and disposal of oil waste into the environment causes serious damage to the environmental ecosystem, the target of processing by the bacteria as a model for remediation of oil contaminated site. Thus, the study was focused on determining the biodegradation percentage of extractable petroleum hydrocarbons as a function of the oil concentration. This research was conducted in a slurry bioreactor with mixed contaminated soil to water ratio of 20:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…has resistant endospores to be more tolerant to high levels of hydrocarbons in soil that has been proved according to the research [34]. High biodegradation capacity at the level above 93 % of crude oil was recorded for the bacterial consortium of Bacillus cereus and Pseudomonas putida bacteria [35].…”
Section: Modeling Of Oil-degradable Bacteria Consortium Capable For B...mentioning
confidence: 85%
“…has resistant endospores to be more tolerant to high levels of hydrocarbons in soil that has been proved according to the research [34]. High biodegradation capacity at the level above 93 % of crude oil was recorded for the bacterial consortium of Bacillus cereus and Pseudomonas putida bacteria [35].…”
Section: Modeling Of Oil-degradable Bacteria Consortium Capable For B...mentioning
confidence: 85%
“…has resistant endospores to be more tolerant to high levels of hydrocarbons in soil that has been proved according to the research (Kidibule et al, 2014). High biodegradation capacity at the level above 93% of crude oil was recorded for the bacterial consortium of Bacillus cereus and Pseudomonas putida bacteria (Tuhuloula et al, 2019). Jussila et al (2007) reported Pseudomonas aeruginosa JI104 must be an effective utilizing and catechol-positive bacteria having the xylEgene participated in the destruction of aromatic hydrocarbons (xylE, BTEX destruction).…”
Section: Modeling Of Oil-degradable Bacteria Consortium Capable For B...mentioning
confidence: 88%
“…Penurunan konsentrasi xylene sejalan dengan kenaikan populasi bakteri di dalam bioreaktor. Hasil yang sama juga didapatkan pada penelitian mengenai biodegradasi EPH dengan menggunakan konsorsium Bakteri, dimana bakteri memanfaatkan hidrokarbon sebagai support growth [10]. Semakin meningkat populasi bakteri maka akan menurunkan jumlah substrat di dalam bioreaktor.…”
Section: Kondisi Awal Tanah Tercemar Minyak Bumiunclassified